1995
DOI: 10.1007/bf00231718
|View full text |Cite
|
Sign up to set email alerts
|

Directional specificity of postural muscles in feed-forward postural reactions during fast voluntary arm movements

Abstract: Healthy subjects performed bilateral fast shoulder movements in different directions while standing on a force platform. Anticipatory postural adjustments were seen as changes in the electrical activity of postural muscles as well as displacements of the center of pressure and center of gravity. Postural muscle pairs of agonist-antagonist commonly demonstrated triphasic patterns starting prior to the first electromyographic (EMG) burst in the prime-mover muscle. Proximal postural muscles demonstrated the large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
261
5
12

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(305 citation statements)
references
References 27 publications
27
261
5
12
Order By: Relevance
“…That study demonstrated a delay in activation of the erector spinae muscle at T7 in individuals with vertebral fractures by 50 ms, and a reliance on trunk muscle co-contraction to maintain equilibrium. Co-contraction contrasts to the alternating trunk muscle activity patterns reported in younger populations during similar tasks [2].…”
Section: Discussionmentioning
confidence: 81%
“…That study demonstrated a delay in activation of the erector spinae muscle at T7 in individuals with vertebral fractures by 50 ms, and a reliance on trunk muscle co-contraction to maintain equilibrium. Co-contraction contrasts to the alternating trunk muscle activity patterns reported in younger populations during similar tasks [2].…”
Section: Discussionmentioning
confidence: 81%
“…The anticipatory response of the trunk muscles is associated with movement of the upper limb. Contraction of either the erector spinae before upper-limb flexion or contraction of the rectus abdominis preceding upper-limb extension were shown [34].…”
Section: Discussionmentioning
confidence: 99%
“…When explicitly manifest, they are characterized by the parallel activation of muscles in different body segments, are scaled with the intensity of the prime movement (Aruin and Latash 1996), and can be reduced or abolished when the biomechanical context is modified (Aruin et al 1998). Further, their timing and spatial distribution may vary when the surrounding conditions or some feature of the movement (e.g., direction) is changed (Aruin and Latash 1995;Nashner and Forssberg 1986). This allows one to imagine that, even when a manifest intervention of the anticipatory postural activities is not required, subthreshold effects may nevertheless take place.…”
Section: Discussionmentioning
confidence: 99%